2021
DOI: 10.1186/s40645-021-00451-6
|View full text |Cite
|
Sign up to set email alerts
|

Natural and experimental high-pressure, shock-produced terrestrial and extraterrestrial materials

Abstract: Hypervelocity impacts are among the fundamental phenomena occurring during the evolution of the solar system and are characterized by instantaneous ultrahigh pressure and temperature. Varied physicochemical changes have occurred in the building blocks of celestial bodies under such extreme conditions. The constituent material has transformed into a denser form, a high-pressure polymorph. The high-pressure polymorph is also thought to be the constituent of the deep Earth’s interior. Hence, experiments using a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 265 publications
(317 reference statements)
0
7
0
Order By: Relevance
“…The variability of shocked basement rocks within several suevite occurrences scattered around the Ries crater was reported by von Engelhardt (1997). A detailed report with a chronological recovering of recently discovered shock-induced high-pressure phases in both terrestrial and extraterrestrial rocks is given by Miyahara et al (2021).…”
Section: Introductionmentioning
confidence: 80%
“…The variability of shocked basement rocks within several suevite occurrences scattered around the Ries crater was reported by von Engelhardt (1997). A detailed report with a chronological recovering of recently discovered shock-induced high-pressure phases in both terrestrial and extraterrestrial rocks is given by Miyahara et al (2021).…”
Section: Introductionmentioning
confidence: 80%
“…The L6 chondrites tend to statistically exhibit higher shock stages than other chondrite groups (Bischoff et al, 2019; Miyahara et al, 2021). Furthermore, although several studies seem to indicate a catastrophic breakup event of the L chondrites parent body occurred about 470 Ma ago (Korochantseva et al, 2007; Schmitz et al, 2001; Swindle et al, 2014), the dynamics of this impact are still not constrained.…”
Section: Samples and Analytical Methodsmentioning
confidence: 98%
“…Such minerals usually form under ultrahigh-pressure conditions (e.g., meteorite impacts and in planetary interiors). Mineralogists have tried to find high-pressure minerals in meteorite impact craters and extraterrestrial samples (e.g., meteorites and samples returned by spacecraft) to understand hypervelocity impacts during the evolution of the solar system and the structure and dynamics of the inner Earth . However, some high-pressure minerals are nanoscale and distributed heterogeneously on the microscale, so nanoscale mineral characterization technology (e.g., TEM) is critical to their identification and study.…”
Section: Mineral Structure At the Nanoscalementioning
confidence: 99%
“…However, some high-pressure minerals are nanoscale and distributed heterogeneously on the microscale, so nanoscale mineral characterization technology (e.g., TEM) is critical to their identification and study. TEM–SAED combined with FIB techniques has greatly aided the study of high-pressure mineralogy in past decades. For example, it has been determined that the pressure and temperature of impact (25–45 GPa and 800–900 °C) at the Xiuyan impact crater in China were sufficient to decompose ankerite [Ca­(Fe 2+ , Mg)­(CO 3 ) 2 ] and form nanoscale diamond in the absence of another reductant, and maohokite, which is a new nanoscale postspinel polymorph of MgFe 2 O 4 , was formed by shocked genesis . Chen et al suggested that diamond is the dominant form of carbon in the lower mantle and maohokite is an important constituent mineral of the lower mantle .…”
Section: Mineral Structure At the Nanoscalementioning
confidence: 99%